Edukasi dengan inovasi produk pangan berbasis daun kelor sebagai upaya pencegahan stunting pada anak - Anggunan, Anggunan; Pangestu, Herwindu Danu; Moch Adytia Pangestu, Moch Adytia; Emelianti, Dipsi; Andini, Mutia; Ludfi, Nyimas Zazkia; Sari, Ni Wayan Widia; Amanda, Dania Tri (JOURNAL of Public Health Concerns, 2025)
Background: Stunting in Indonesia remains a serious challenge to improving child health, with a national prevalence reaching 21.6% in 2022. Early prevention efforts through nutritional improvement and the use of balanced, nutritious local foods are essential. The Moringa oleifera plant, rich in essential nutrients, has significant potential as a functional food ingredient to prevent stunting. In Pekon Belu, Tanggamus Regency, the use of Moringa is still limited despite its abundant availability. This study analyzes innovative local food products based on Moringa leaves, such as pudding and dumplings, as an adaptive, affordable, and sustainable nutritional intervention strategy to support stunting prevention in children. Purpose: To provide education on innovative processed food products based on Moringa leaves, such as pudding and dumplings, as an effort to increase children's nutritional intake. Method: The activity was conducted in 2025 in Pekon Belu, West Kota Agung District, Tanggamus Regency. It involved 63 participants, consisting of 3 pregnant women, 6 infants aged 0–12 months, 15 toddlers, and 43 children. The activity included education on the local potential of the Moringa plant and outreach on its nutritional content to meet nutritional needs that can contribute to stunting prevention. A simple organoleptic test was conducted on 20 children regarding processed foods, namely pudding and dumplings made from Moringa leaves. The simple organoleptic assessment consisted of assigning a score to each statement, with 1=like and 0=dislike. Results: Of the 15 toddlers, data obtained indicated that 6 children (40.0%) had symptoms of stunting. Based on the simple organoleptic assessment data by the 20 children, the pudding product received a score of 4.2 points for taste, 4.0 points for color, and 4.5 points for texture, with an acceptance rate of 85%. Meanwhile, processed siomay products obtained scores of 4.0 points for taste, 3.8 points for color, and 4.2 points for texture, with an acceptance rate of 80%. Conclusion: Educational activities involving innovative food processing using moringa leaves as the main ingredient in pudding and dumplings have made a positive contribution as an effective and affordable locally-based nutrition intervention for the community. Suggestion: Further research through laboratory analysis and trials with larger samples is needed to strengthen the scientific evidence regarding the nutritional content of moringa products. Furthermore, the development of a variety of moringa-based products is necessary to expand nutritious food choices to support stunting prevention. This product has the potential to be a stunting prevention strategy because it suits children's tastes, is easily accessible, and is economical. Keywords: Dumpling; Moringa leaves; Nutrition; Pudding; Stunting Pendahuluan: Masalah stunting di Indonesia masih menjadi tantangan serius dalam peningkatan kualitas kesehatan anak, dengan prevalensi nasional mencapai 21.6% pada tahun 2022. Upaya pencegahan sejak dini melalui perbaikan gizi dan pemanfaatan pangan lokal bergizi seimbang sangat diperlukan. Tanaman kelor (Moringa oleifera), yang kaya akan zat gizi penting, memiliki potensi besar sebagai bahan pangan fungsional untuk mencegah stunting. Di Pekon Belu, Kabupaten Tanggamus, pemanfaatan kelor masih terbatas meski ketersediaannya melimpah. Penelitian ini menganalisis inovasi produk pangan lokal berbasis daun kelor, seperti puding dan siomay, sebagai strategi intervensi gizi yang adaptif, terjangkau, dan berkelanjutan dalam mendukung pencegahan stunting pada anak. Tujuan: Memberikan edukasi dengan inovasi produk olahan makanan berbasis daun kelor berupa puding dan siomay sebagai upaya peningkatan asupan nutrisi bergizi pada anak. Metode: Kegiatan dilaksanakan pada tahun 2025 di Pekon Belu, Kecamatan Kota Agung Barat, Kabupaten Tanggamus. Melibatkan 63 peserta, terdiri dari 3 ibu hamil, 6 bayi usia 0–12 bulan, 15 balita, dan 43 anak-anak. Kegiatan berupa edukasi pemanfaatan potensi lokal tanaman kelor dan sosialisasi kandungan gizi sebagai pemenuhan kebutuhan kecukupan gizi yang dapat berkontribusi dalam pencegahan stunting. Dilakukan uji organoleptik sederhana pada 20 anak terkait makanan olahan berupa puding dan siomay dari daun kelor. Penilaian organoleptik sederhana berupa pemberian nilai skor dalam setiap pernyataan nilai 1=menyukai, dan 0=tidak menyukai. Hasil: Dari sebanyak 15 balita, mendapatkan data sebanyak 6 anak-anak (40.0%) terindikasi memiliki gejala stunting. Berdasarkan data penilaian organoleptik sederhana oleh 20 anak untuk produk olahan puding memperoleh skor pada aspek rasa 4.2 poin, aspek warna 4.0 poin, dan aspek tekstur 4.5 poin, dengan tingkat penerimaan mencapai 85%. Sedangkan untuk produk olahan siomay memperoleh skor pada aspek rasa 4.0 poin, aspek warna 3.8 poin, dan aspek tekstur 4.2 poin, dengan tingkat penerimaan mencapai 80%. Simpulan: Kegiatan edukasi dengan inovasi pengolahan pangan menggunakan daun kelor sebagai bahan utama dalam puding dan siomay memberikan kontribusi positif sebagai intervensi gizi berbasis potensi lokal yang efektif dan terjangkau pada masyarakat. Saran: Penelitian lanjutan melalui analisis laboratorium dan uji coba dengan sampel lebih besar diperlukan untuk memperkuat bukti ilmiah terkait kandungan gizi produk kelor. Selain itu, pengembangan ragam produk berbasis kelor perlu dilakukan guna memperluas pilihan pangan bergizi dalam mendukung pencegahan stunting. Produk ini berpotensi menjadi strategi pencegahan stunting karena sesuai selera anak, mudah diakses, dan ekonomis.